An Ethiopian Grammar Treatise (Säwasəw) in the Manuscript NLR Eth. n.s. 11 as a Textbook for the Future Metropolitan of Ethiopia - Ekaterina Gusarova (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This article deals with a remarkable example of Ethiopian grammatical and lexicographic treatise (Säwasəw) kept in the Manuscript Department of the National Library of Russia in St Petersburg. The tradition of making compilations of this kind goes back in Ethiopia to the period of the foundation of the Gondarine Kingdom in the 17th century AD, which was characterised by general fl ourishing of culture in the region. In all probability, this genre was borrowed from the Coptic Arabic tradition. Initially, such treatises were created and used as glossaries for Biblical and liturgical texts. Later, they came to be applied for education purposes as textbooks in monastic and church traditional schools. Such manuscript handbooks included lists of Ge’ez words with parallel Amharic translations and often grammatical forms of verbs. The grammar treatise in question is notable not only for a series of specifi c features, specifi c both to its contents and structure, but also with its colophon, that shed light on the history of creation of the manuscript and its further fate. It was compiled outside Ethiopia, in the bosom of the Coptic Church. This circumstance explains the presence of some peculiarities in comparison with the most common examples of such lists. Glosses in Ge’ez are translated not only in Amharic but in Arabic as well. The manuscript was intended for Peter VII, the Coptic Alexandrian Patriarch in 1809–1852, who was initially prepared to become the Metropolitan of the Ethiopian Church. Later in Ethiopia, which was passing through the sorrowful period of political disintegration, there was a need in a new head of the Church, who had to be ordained and sent to that country by Peter VII.